2016
DOI: 10.1080/1331677x.2016.1193949
|View full text |Cite
|
Sign up to set email alerts
|

Differences in consumer decision-making styles among selected south-east European countries

Abstract: Fast changes in retailing and complex consumer decision-making processes have increased the need for additional investigation of differences and similarities in consumer decision-making styles (CDMS) in various countries. This paper tests the reliability and validity of Sproles and Kendall's Consumer Style Inventory (CSI) instrument, identifies and compares CDMS in Croatia, Bosnia and Herzegovina and Macedonia (FYR). Data obtained from surveys conducted among university students in observed countries (n = 1.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…This has been suggested by Fan and Xiao (1998), when adapting the original CSI for China. It was also suggested by Anić et al (2016) within a multicountry comparison from the Western Balkans. Third, our analysis of previous multi-country CDMS studies (in Table 1) shows that we need to question prior evidence regarding the general applicability of Sproles and Kendall's (1986) eight-factor CDMS framework in diverse multicountry and regional contexts (Hafstrom et al, 1992).…”
Section: Theoretical Implicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…This has been suggested by Fan and Xiao (1998), when adapting the original CSI for China. It was also suggested by Anić et al (2016) within a multicountry comparison from the Western Balkans. Third, our analysis of previous multi-country CDMS studies (in Table 1) shows that we need to question prior evidence regarding the general applicability of Sproles and Kendall's (1986) eight-factor CDMS framework in diverse multicountry and regional contexts (Hafstrom et al, 1992).…”
Section: Theoretical Implicationsmentioning
confidence: 85%
“…We have shown that significant inter-and intra-regional differences exist when it comes to CDMS of young-adult consumers in East Asia and Central and Eastern Europe; and that regional differences are not bigger than country differences. This carries implications for understanding regional boundaries of the so-called global consumer culture (Merz et al, 2008) and CDMS research (Anić et al, 2016;Ding et al, 2018;Rašković et al, 2016). Of course, further research should be conducted to what degree are such differences driven by national or personal culture orientations; but this was beyond the scope of our study.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…However, the conclusions should be derived only for a Croatian population, which represents a limitation of the study. Consumer behaviour is still heterogeneous due to cultural and income differences among countries (Anić et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At individual level, boundaries of rationality are characteristics of the individual, heuristics and biases forming a subjective rationality, namely a unique set of boundaries that lead to a specifi c choice for each individual (Kostelić, 2017). Davis et al (2007) defi ne the nexus of personality traits and the decision -making. Relevant individual's characteristics for economic decision -making are composed of psychological, sociological and economical elements.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…For more than 35 years, the CDMS concept developed by Sproles and Kendall (1986) have been used in numerous research studies. So far, this theoretical framework has provided valuable insights into consumers' characteristics and their purchasing patterns when selecting a particular product type, as well as consumer decision-making styles across different populations, cultural and economic contexts, various product categories, and retail formats (e.g., Mohsenin et al, 2018;Bakewell and Mitchell, 2003;Lysonski, Durvasula and Zotos, 1996;Yaşin, 2015;Anić et al, 2016;Cowart and Goldsmith, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%